Equity and Justice in Climate Action Planning: The Challenge of Evaluation - Swanson, Kayleigh (Canadian Planning and Policy / Aménagement et politique au Canada, 2023)
Climate action plans help cities respond to climate change, but the efficacy of these plans for advancing social justice remains unclear. Although there is agreement on the attributes of a quality plan, our ability to evaluate whether planning outcomes are equitable and just is underdeveloped. I consider how communities should decide the meaning and application of the concepts of equity and justice, and how plan evaluation approaches could be modified to better assess the efficacy of plans for advancing social justice goals. I recommend the use of context-specific justice principles, and an approach that makes plan efficacy a more prominent feature of plan evaluation.